Irinotecan toxicity during treatment of metastatic colorectal cancer: focus on pharmacogenomics and personalized medicine. Issue 2 (April 2020) - Paulík, Adam; Nekvindová, Jana; Filip, Stanislav
Colorectal cancer, one of the most frequent types of cancer worldwide, has a high mortality rate. Irinotecan (CPT-11) has been approved for the treatment of advanced or metastatic disease either as a single agent or, more commonly, as part of combined chemotherapeutic regimens. Treatment with irinotecan is often accompanied by severe toxicity (e.g. neutropenia and diarrhea) that can result in treatment interruption or cessation, thus jeopardizing the patient's prognosis and quality of life. Irinotecan is bioactivated into its metabolite SN-38, which is subsequently detoxified by uridine diphosphate-glucuronosyl transferases (mainly UGT1A1). Further, ABC transporters (i.e. ABCB1, ABCC1–ABCC6, and ABCG2) are responsible for drug efflux into bile and urine whereas OATP transporters (SLCO1B1) enable its influx from blood into hepatocytes. Genetic polymorphisms in these enzymes/pumps may result in increased systemic SN-38 level, directly correlating with toxicity. Contemporary research is focused on the clinical implementation of genetic screenings for validated gene variations prior to treatment onset, allowing tailored individual doses or treatment regimens.